Immunoglobulin M Monoclonal Gammopathies of Clinical Significance - Girard, Louis-Pierre; Soekojo, Cinnie Yentia; Ooi, Melissa; Chng, Wee Joo; de Mel, Sanjay (Frontiers in Oncology, 2022)
Immunoglobulin M monoclonal gammopathy of undetermined significance (MGUS) comprises 15-20% of all cases of MGUS. IgM MGUS is distinct from other forms of MGUS in that the typical primary progression events include Waldenstrom macroglobulinaemia and light chain amyloidosis. Owing to its large pentameric structure, IgM molecules have high intrinsic viscosity and precipitate more readily than other immunoglobulin subtypes. They are also more commonly associated with autoimmune phenomena, resulting in unique clinical manifestations. Organ damage attributable to the paraprotein, not fulfilling criteria for a lymphoid or plasma cell malignancy has recently been termed monoclonal gammopathy of clinical significance (MGCS) and encompasses an important family of disorders for which diagnostic and treatment algorithms are evolving. IgM related MGCS include unique entities such as cold haemagglutinin disease, IgM related neuropathies, renal manifestations and Schnitzler’s syndrome. The diagnostic approach to, and management of these disorders differs significantly from other categories of MGCS. We describe a practical approach to the evaluation of these patients and our approach to their treatment. We will also elaborate on the key unmet needs in IgM MGCS and highlight potential areas for future research.